Principal provisions of the decommissioning concept for the WWR-M research reactor - Yu. M. Lobach; E. D. Luferenko; M. V. Lysenko; V. M. Shevel (Ядерна фізика та енергетика)
The decommissioning Concept for WWR-M research reactor is developed to meet the requirements of the current Ukrainian legislation. The main goal of the Concept is to provide a strategic stage of the work planning, including all the required justifications with a sufficient level of detail. It will allow during the next planning stage to develop the decommissioning project and other documents required to obtain the decommissioning license. The Concept is the institutional and technical document, which defines and substantiates the basic administrative, organizational, and technical measures for the preparation and implementation of the reactor decommissioning. It also describes the main activities and works, defines the procedure, conditions for their implementation and provision, and planned deadlines.